Gene delivery of a modified antibody to Aβ reduces progression of murine Alzheimer's disease. - Bradford M Elmer; Kurt A Swanson; Dinesh S Bangari; Peter A Piepenhagen; Errin Roberts; Tatyana Taksir; Lei Guo; Maria-Carmen Obinu; Pascal Barneoud; Susan Ryan; Bailin Zhang; Laurent Pradier; et al. (PLoS ONE)
Antibody therapies for Alzheimer's Disease (AD) hold promise but have been limited by the inability of these proteins to migrate efficiently across the blood brain barrier (BBB). Central nervous system (CNS) gene transfer by vectors like adeno-associated virus (AAV) overcome this barrier by allowing the bodies' own cells to produce the therapeutic protein, but previous studies using this method to target amyloid-β have shown success only with truncated single chain antibodies (Abs) lacking an Fc domain. The Fc region mediates effector function and enhances antigen clearance from the brain by neonatal Fc receptor (FcRn)-mediated reverse transcytosis and is therefore desirable to include for such treatments. Here, we show that single chain Abs fused to an Fc domain retaining FcRn binding, but lacking Fc gamma receptor (FcγR) binding, termed a silent scFv-IgG, can be expressed and released into the CNS following gene transfer with AAV. While expression of canonical IgG in the brain led to signs of neurotoxicity, this modified Ab was efficiently secreted from neuronal cells and retained target specificity. Steady state levels in the brain exceeded peak levels obtained by intravenous injection of IgG. AAV-mediated expression of this scFv-IgG reduced cortical and hippocampal plaque load in a transgenic mouse model of progressive β-amyloid plaque accumulation. These findings suggest that CNS gene delivery of a silent anti-Aβ scFv-IgG was well-tolerated, durably expressed and functional in a relevant disease model, demonstrating the potential of this modality for the treatment of Alzheimer's disease.